Reducing agricultural nitrate leaching : investigating the performance of denitrification bioreactors in New Zealand conditions : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Science [Agriculture] at Massey University - Ratcliffe, Harry (Massey University, 2023)
Denitrifying woodchip bioreactors are a tool that is used in the agriculture sector to reduce undesired nitrate-nitrogen (NO₃-N) concentrations in subsurface drainage water before entering downstream environments. As well as their ability to reduce the NO₃-N pollutant, denitrifying bioreactors tend to produce other unwanted pollutants such as nitrogen dioxide (N₂O), carbon dioxide (CO₂), and methane (CH₄). This thesis presents research from 2 pre-installed denitrification bed bioreactors in the Manawatu-Whanganui region of New Zealand. The aim of this research was to measure the performance of these bioreactors in terms of nitrate removal rates and nitrate removal efficiency, as well as measuring any unwanted pollutants produced. Nitrate removal performance was assessed by measuring the nitrate concentrations flowing into the bioreactor and comparing them to the nitrate concentrations flowing out. The difference between these values, per unit time, is the nitrate removal rate (NRR). To recreate different New Zealand seasonal conditions different flow rates were changed, hence, the length of time the dissolved solutes remained in the bioreactors (hydraulic retention time or HRT) also changed. Measurements were undertaken to see if these changes in flow rates had any effect on nitrate removal, N₂O, CO₂, and CH₄ production. Results indicated that during the spring of 2022, the denitrifying bioreactors removed an average of 2.25 and 3.70 grams of NO₃-N per m³ of water per day, with an average nitrate removal efficiency (NRE) of 76.3 and 76.5%. Relatively smaller fractions of 1.81 and 0.77% of the NO₃-N removed was converted to N₂O within the bioreactors. Of the N₂O produced, 99.5 and 99.8% was dissolved and leached in the outflow, whilst 0.5 and 0.2% was released as a gas. This supports previous literature from Rivas et al., (2019), stating that bioreactors produce high NO₃-N removal rates with relatively low N₂O emissions, with the main export pathway of N₂O via outflow of water in dissolved form. Results also indicated that, for both bioreactors, there is strong correlation that as HRT decreased, NRR exponentially increased. As HRT increased, the ratio of N₂O-N produced to NO₃-N removed decreased, with an R-squared value of 0.8007 proving significant correlation. The average CO₂ produced was 6.13 and 0.441 g CO₂-C/m³ /day and the average CH4 produced was 5.10E-04 and 3.17E-03 g CH₄-C/m³ /day. The concentrations of CO₂ and CH₄ produced by the bioreactor were difficult to compare to average concentrations produced from agricultural land in New Zealand due to varying climate, soil, and pasture species. Varying the HRTs of the 2 bioreactors produced no significant effect on CO₂ or CH₄ production.
Keywords: 409901 Agricultural engineering